New evidence on determinants of IP litigation: A market-based approach - Dirk Czarnitzki; Kristof van Criekingen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
We contribute to the economic literature on patent litigation by taking a new perspective. In the past, scholars mostly focused on specific litigation cases at the patent level and related technological characteristics to the event of litigation. However, observing IP disputes suggests that not only technological characteristics may trigger litigation suits, but also the market positions of firms, and that firms dispute not only about single patents but often about portfolios. Consequently, this paper examines the occurrence of IP litigation cases in Belgian firms using the 2013 Community Innovation Survey with supplemental information on IP litigation and patent portfolios. The rich survey information regarding firms' general innovation strategies enables us to introduce market-related variables such as sales with new products as well as sales based mainly on imitation and incremental innovation. Our results indicate that when controlling for firms' IP portfolio, the composition of turnover in terms of innovations and imitations has additional explanatory power regarding litigation propensities. Firms with a high turnover from innovations are more likely to become plaintiffs in court. Contrastingly, firms with a high turnover from incremental innovation and imitation are more likely to become defendants in court, and, moreover, are more likely to negotiate settlements outside of court.
urn:nbn:de:bsz:180-madoc-456631
Keywords: O31; O34; 330; IP litigation; patenting; innovation; imitation